Implementation of Waste Management Policy in Simokerto District, Surabaya City - Cahyono, Hendrik; Nawangsari, Ertien Rining (Formosa Journal of Multidisciplinary Research, 2024)
Environmental problems, including the waste problem, have become a serious challenge in many countries, including Indonesia. Every day, humans produce waste from various activities, which has not been completely resolved. This study aims to analyze waste management policies in the city of Surabaya, using a qualitative method based on Edward III's theory which includes four indicators: Human Resources, Information, Authority, and Facilities. The results show that even though the policy has been running well, there are still people who have not maintained cleanliness and understood waste management properly.